Synthesis of the Hydroxamate Siderophore Nα-Methylcoprogen B in Scedosporium apiospermum Is Mediated by sidD Ortholog and Is Required for Virulence - Le Govic, Yohann; Havlíček, Vladimir; Capilla, Javier; Luptáková, Dominika; Dumas, Dayana; Papon, Nicolas; Le Gal, Solène; Bouchara, Jean-Philippe; Vandeputte, Patrick (Frontiers in Cellular and Infection Microbiology, 2020)
Scedosporium species rank second among the filamentous fungi capable to colonize chronically the respiratory tract of patients with cystic fibrosis (CF). Nevertheless, there is little information on the mechanisms underpinning their virulence. Iron acquisition is critical for the growth and pathogenesis of many bacterial and fungal genera that chronically inhabit the CF lungs. In a previous study, we showed the presence in the genome of Scedosporium apiospermum of several genes relevant for iron uptake, notably SAPIO_CDS2806, an ortholog of sidD, which drives the synthesis of the extracellular hydroxamate-type siderophore fusarinine C (FsC) and its derivative triacetylfusarinine C (TAFC) in Aspergillus fumigatus. Here, we demonstrate that Scedosporium apiospermum sidD gene is required for production of an excreted siderophore, namely, Nα-methylcoprogen B, which also belongs to the hydroxamate family. Blockage of the synthesis of Nα-methylcoprogen B by disruption of the sidD gene resulted in the lack of fungal growth under iron limiting conditions. Still, growth of ΔsidD mutants could be restored by supplementation of the culture medium with a culture filtrate from the parent strain, but not from the mutants. Furthermore, the use of xenosiderophores as the sole source of iron revealed that S. apiospermum can acquire the iron using the hydroxamate siderophores ferrichrome or ferrioxamine, i.e., independently of Nα-methylcoprogen B production. Conversely, Nα-methylcoprogen B is mandatory for iron acquisition from pyoverdine, a mixed catecholate-hydroxamate siderophore. Finally, the deletion of sidD resulted in the loss of virulence in a murine model of scedosporiosis. Our findings demonstrate that S. apiospermum sidD gene drives the synthesis of a unique extracellular, hydroxamate-type iron chelator, which is essential for fungal growth and virulence. This compound scavenges iron from pyoverdine, which might explain why S. apiospermum and Pseudomonas aeruginosa are rarely found simultaneously in the CF lungs.